Sozialräumliche Konflikte in der unternehmerischen Stadt: Eine Berliner Fallstudie über städtische Bewegungspolitik unter den Bedingungen von New Public Management - Lebuhn, Henrik (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2007)
Entrepreneurial urban politics not only aim at up-grading a locality for interurban competition. Under the label of New Public Management, they also remodel the city administration according to economic criteria of efficency. As a result, the political arena for urban social movements is undergoing severe changes. In the case of Berlin, New Public Management reforms seem to disadvantage grassroots groups that protest the privatization of public space, and lead to a political gap between social movements and left political parlamentarians.